Blood Pressure Regulation by the Carotid Sinus Nerve: Clinical Implications for Carotid Body Neuromodulation - Conde, Silvia V.; Sacramento, Joana F.; Melo, Bernardete F.; Fonseca-Pinto, Rui; Romero-Ortega, Mario I.; Guarino, Maria P. (Frontiers in Neuroscience, 2022)
Chronic carotid sinus nerve (CSN) electrical modulation through kilohertz frequency alternating current improves metabolic control in rat models of type 2 diabetes, underpinning the potential of bioelectronic modulation of the CSN as a therapeutic modality for metabolic diseases in humans. The CSN carries sensory information from the carotid bodies (CB), peripheral chemoreceptor organs that respond to changes in blood biochemical modifications like hypoxia, hypercapnia, acidosis, and hyperinsulinemia. In addition, the CSN also delivers information from carotid sinus baroreceptors - mechanoreceptor sensory neurons directly involved in the control of blood pressure - to the central nervous system. The interaction between these powerful reflex systems – chemoreflex and baroreflex, whose sensory receptors are in anatomical proximity, may be regarded as a drawback to the development of selective bioelectronic tools to modulate the CSN. Herein we aimed to disclose carotid sinus nerve influence on cardiovascular regulation, particularly under hypoxic conditions, and we tested the hypothesis that neuromodulation of the carotid sinus nerve, either by electrical stimuli or by surgical means, does not significantly impact blood pressure. Experiments were performed in Wistar rats aged 10-12 weeks. No significant effects of acute hypoxia were observed in systolic or diastolic blood pressure or heart rate, although there was a significant activation of the cardiac sympathetic nervous system. We concluded that chemoreceptor activation by hypoxia leads to an expected increase in sympathetic activity accompanied by compensatory regional mechanisms that assure blood flow to regional beds and maintenance of hemodynamic homeostasis. Upon surgical denervation or electrical block of the CSN the increase in cardiac SNS activity in response to ischemic hypoxia was lost and there were no significant changes in blood pressure in comparison to control animals. We concluded that the responses to hypoxia and vasomotor control short-term regulation of blood pressure are dissociated, in terms of hypoxic response, but integrated to generate an effector response to a given change in arterial pressure.